The effects of pelvic alignment versus hip joint mobility on shoulder internal rotation deficit and torque production – A blinded randomized controlled study. (November 2018) - Nourbakhsh, Mohammad Reza; Bluestein, Ashley; Power, Richard; Underwood, Shaun; White, Leanna
Highlights: Glenohumeral Internal Rotation Deficit (GIRD) is affected by limited hip mobility. Hip joint mechanics also are affected by pelvic alignment. Is GIRD more associated with limited hip mobility or pelvic malalignment. Exercises for pelvic alignment are more effective for GIRD than exercises for hip.